2020
DOI: 10.5513/jcea01/21.3.2376
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the EPNs (Heterorhabditis bacteriophora) on sugar beet larvae (Bothynoderes punctiventris)

Abstract: The effectiveness of entomopathogenic nematode (EPN) Heterorhabditis bacteriophora Poinar, 1976 (Nematoda: Heterorhabditidae) infective juveniles (IJs) on sugar beet weevil (Bothynoderes punctiventris Germar, 1824 (Coleoptera: Curculionidae)) larvae was investigated during two-year (2014-2015). The field study was conducted to assess EPNs potential for use in practice. In field experiments, three doses of nematodes were used and an untreated control. In the conditions of moderate larval attack (average infesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Apart from the use of nematodes [ 27 , 28 ], which were only used against the larvae of the sugar beet weevil A. punctiventris in the soil, this large-scale study is one of the first in almost a hundred years (except a few studies using Beauveria bassiana [ 14 , 15 ]) to test the use of a biologically based insecticide against the weevil pest. We aimed to test the effectiveness of a preventive use of the entomopathogenic fungus Metarhizium brunneum against the weevil in all stages of its development.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the use of nematodes [ 27 , 28 ], which were only used against the larvae of the sugar beet weevil A. punctiventris in the soil, this large-scale study is one of the first in almost a hundred years (except a few studies using Beauveria bassiana [ 14 , 15 ]) to test the use of a biologically based insecticide against the weevil pest. We aimed to test the effectiveness of a preventive use of the entomopathogenic fungus Metarhizium brunneum against the weevil in all stages of its development.…”
Section: Discussionmentioning
confidence: 99%
“…During the subsequent maturation feeding phase, females and males consume sugar beet seedlings or young plants, resulting in their destruction [4][5][6]. The feeding activity can damage entire fields, often requiring reseeding [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports from Poland, Eastern Croatia, and Hungary indicate that the pest has spread further towards Central Europe and become increasingly destructive [2,7,9]. In Eastern Austria, a mass outbreak led to the loss of almost a quarter of the total sugar beet area in 2018, and the sugar beet weevil continued to cause economic damage in subsequent years [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this approach succeeded in reducing pest populations, the authors concluded that trapping as an isolated measure is not efficient enough to replace chemical control of the sugar beet weevil. Other alternative measures such as the use of entomopathogenic nematodes as natural enemies for biological control of A. punctiventris have not yet been investigated sufficiently and are not available in practice (Sursuluk 2008;Drmic et al 2020).…”
Section: Introductionmentioning
confidence: 99%